Femtoscopy of the Matter Distribution in the Proton - Krein, Gastão [UNESP] (Springer Nature, 2023)
This communication is a follow-up on our previous study [Few Body Syst. 61, 49 (2020)] suggesting the use of femtoscopic measurements of J/ ψ -proton correlation functions in high-energy hadron collisions to access information on the origin of the proton’s mass. The QCD multipole expansion allows us to express the J/ ψ -proton scattering amplitude in terms of the product of the J/ ψ chromopolarizability and a scalar gluon gravitational (GFF) form factor. The scalar gluon GFF gives the gluonic contribution to the nucleon mass and determines the corresponding matter radius. We show that J/ ψ -proton femtoscopic correlation function displays clear sensitivity to the scalar gluon GFF for a wide range of the J/ ψ chromopolarizability.